Formalization of selection of contract-organizational project delivery strategy - Bugrov, Olexander; Bugrova, Olena (Eastern-European Journal of Enterprise Technologies, 2018)
The formalized system to select a strategy for the implementation of a capital construction project was developed. This is important because an error in making a strategic decision (in an intuitive rather than formalized way) critically affects the further course of events on a project and usually cannot be fixed through the efforts of tactical and operative control. Throughout the whole range of strategies, a number of those, which have characteristic features, and therefore affect specifically project initiators, were determined. Discreteness of the field of alternatives gives a possibility to avoid "fuzziness" in making decisions on the most appropriate strategy. The system became unified through the separation of two elements in it: (1) variable (movable) context that recognizes the features a specific business situation and the specificity of the analyzed project, (2) constant (unmovable) context that reflects the properties of each of the alternative strategies. The business process of comparative analysis involves three stages: assessment of the organization maturity, identification of the market development level, determining project priorities and conformity of a priority complex with the profiles of key contract-organizational models. The first stage gives an answer to the question: "Is it worth following a multi-variant contract-organizational scheme of project management?", the second one solves the problem "Is it worthwhile applying IPD in the current situation?" and the third one gives a response to the question "Which of the contract-organizational models of the analyzed project should be followed?" Thus, the conceptual model reflects all available alternatives of typical strategies that are applied in the international best practices. The total number of key basic contract-organizational alternatives includes 26 strategies. Both the project space, and the field of strategic alternatives are reflected in an integrated coordinate system "time–costs–value–risk" by the conceptual model. The formalized toolset formed the system of the project agreement-organization models COMPAS. The formalized system makes it possible to make unambiguous well-grounded decisions on project delivery strategies, which in practice will lead to better project results.